Initiating the Community Economic Improvement through Intellectual Property Registration of “Robusta Pinogu Coffee” - Ibrahim Ahmad; Hasbir Paserangi (Faculty of Law, Hasanuddin University, 2018)
Robusta Pinogu coffee was well known in both domestic and international markets, with production centers located in Pinogu subdistrict, Bone Bolango Regency, Gorontalo Province, Indonesia. It has unique flavor quality and good reputation in local, national and international markets. Its reputation tends to be counterfeited by irresponsible parties, which would harm producers and consumers of Robusta Pinogu coffee. Related to that, then “Masyarakat Indikasi Geografis Kopi Robusta Pinogu Bone Bolango” (MIG-KRPBB) be aware the need to have geographical indications for Robusta Pinogu coffee. Therefore, MIG-KRPBB submits for registration of geographical indication of Robusta Pinogu coffee to the Government of the Republic of Indonesia through the Ministry of Justice and Human Rights of the Republic of Indonesia based on the prevailing laws and regulations. This research was conducted in Bone Bolango Regency, Gorontalo Province. It is a legal research by using normative and empirical approaches. The results show that the Robusta Pinogu coffee in the market will be more secure than counterfeiting by parties who are not entitled to use the mark of Geographical Indication of Robusta Pinogu Coffee. however, it is expected to realize legal protection in the form of registration of geographical indication of Robusta Pinogu coffee for coffee farmer community so as to increase their economic level.